(Information letter) A method for increasing the antimicrobial activity of nisin - Martynov, Artur; Knish, Oksana; Osolodchenko, Tetyana; Batrak, Olena (Annals of Mechnikov's Institute, 2024)
The compositions showed antimicrobial activity on S. aureus strain № 218 and S. pyogenes strain № 105, which were resistant to all the studied antimicrobial agents and antibiotics. Growth inhibition zones around the wells (well method) ranged from 15 mm to 20 mm when the well was injected with the finished composition of nisin, amlodipine and diclofenac. In the control, where only auxiliary substances (molding agents and solubilizers) were used without diclofenac, amlodipine and nisin, no growth retardation zone was observed. Thus, a pharmaceutical composition containing nisin 0.1-0.5% (w/w), diclofenac sodium 0.2-1.0%, and amlodipine mesylate 0.05-0.15% has a broader spectrum of action on Gram-positive strains of microorganisms. Keywords: Nisin, Diclophenac, Amlodipin, co-cultivation, solid media, taurine, multiresistant microorganisms, Staphylococcus aureus, Streptococcus pyogenes, well method